PRELIMINARY CONSIDERATIONS ON THE REMOVAL OF Fe, Zn AND Mn IONS FROM ACIDIC MINE DRAINAGE USING HYDROXYAPATITE - VARVARA, Simona; POPA, Maria; BOSTAN, Roxana; LANCRANJAN, Alexandra; MOLDOVAN, Marioara; ROŞU, Cristina (Studia Universitatis Babeș-Bolyai Ambientum, 2015)
The present study aimed at evaluating at laboratory-scale the possibility of ability of a synthetic hydroxyapatite in the removal process of metallic ions (Fe, Zn and Mn) from acid mine drainage generated at the abandoned mining perimeter of Gura Minei from Rosia Montana (Alba County, Romania). The water drainage from Gura Minei is acidic (pH = 2.9) and contains high concentrations iron, manganese and zinc. The removal efficiency of metal ions from AMD by hydroxyapatite was determined at different sorbent dosages and contact times, during batch sorption experiments. The composition of the acid mine drainage from Gura Minei before and after the treatment with hydroxyapatite was determined by X-ray fluorescence spectroscopy. In the investigated experimental conditions, adsorption of heavy metal ions from acid mine drainage by hydroxyapatite lay in the following order: Fe > Zn > Mn. About 99.8%, 83.4% and 24.7 % iron, zinc and manganese, respectively were removed from acid water drainage after 300 minutes of contact with 1.5 g synthetic hydroxyapatite.